Письмо хазарского хакана Юстиниану II - Калинина, Т.М. (Хазарский альманах, 2016)
Статья посвящена информации «Книги титулов» арабо-христианского мелькитского историка Х в. Агапия Манбиджского (Х в.) о письме хазарского хакана византийскому императору Юстиниану II (685–695 и 705–711). Схожая история встречается в «Хронографии» византийского монаха Феофана (Х в.). Весьма близкие сюжеты имеются в сирийской Хронике Феофила Эдесского (VIII в.) и в «Истории» Михаила Сирийского (XII в.). Исследователи дискутируют на тему источников информации этих писателей. Считается, что Агапий не пользовался напрямую книгой Феофана, но все указанные авторы опирались на анонимные сирийские хроники VIII в. Феофан привлекал данные трех сирийских хроник 728, 746 и 780 гг. Агапий же брал за основу Хронику 746 г., в которую вошла и Хроника 728 г. Литературный характер истории с письмом хазарского хакана Юстиниану показывает, что рассказ носит, вероятнее всего, легендарный характер, однако отчетливо выражает антиюстиниановские настроения византийского общества. The article is devoted to information of the Arab-Christian historian Agapius from Manbidj (X century) and to the story of Byzantine Theophanes the Confessor (X century) about the letter of the Khazarian Khaqan to the Byzantine emperor Justinian II. The similarity of the data shows a single primary source of this information. Similar stories exist in the Chronicle of Theophilus of Edessa (VIII cent.), and the “History” of Michael the Syrian. The researchers consider that Agapius didn’t use directly by Theofanes’s book. Theophanes relied on three continuing each other, anonymous Chronicles of 728 year, of 746 year and 780 year. Agapius used the Chronicle of 746 year, which included the anonymous Chronicle from Edessa of 728 year. Literary character of the story shows that the stated history, most likely, is legendary. The tonality of the history in all options shows abhorrence to Justinian II and goes back to moods of the Byzantine community.